Application of Direct Controls to Variable–Speed Wind - Schmidt, I. (2007)
The well–known principle of the direct torque control applied mainly to squirrel–cage induction motor drives can be generalized and applied to other machines, quantities, converters and systems. These are: other AC machines (double–fed induction and permanent magnet synchronous machine), active and reactive power, direct power control of the line side converter, direct controls of both of the converters in a DC link inverter. These new fields are investigated in this paper generally and their application to the components of a wind generator practically. The limits of the direct torque control in salient–pole permanent magnet synchronous generator are given. A solution is given for the stability problem of the double–fed induction generator. The systems are investigated by simulation, the results show the excellent performance of the proposed controls.